Perceived subjective versus objective knowledge: Consumer valuation of genetically modified certification on food producing plants. - Alicia Rihn (Public Library of Science (PLoS), 2021)
Previous research has identified subjective and objective knowledge as determinants of consumers' acceptance of genetically modified organisms (GMO) in the medical and food industries. In contrast to a large body of literature on the effects of attitudes or knowledge on food preferences, the extent to which consumers' knowledge affects their valuation of non-GMO food producing plants (i.e., plants grown for food or ornamental purposes) is less understood. This manuscript investigates the relationship between consumers' knowledge of relevant non-GMO certification programs and their acceptance and willingness-to-pay (WTP) for non-GMO plants. The first study used an Internet respondent panel and choice experiment, while the second study utilized an in-person experimental auction. In line with previously reported low public acceptance of genetically modified food products, respondents were receptive of and willing to pay premiums for non-GMO food producing plants. This study found that subjective and objective knowledge impacted the premiums for non-GMO labels, with the high subjective and low objective knowledge group generating the highest WTP. Low subjective and low objective knowledge resulted in the lowest WTP. Findings suggest a disconnect between subjective and objective knowledge of non-GMO certification programs, which in turn influences consumer valuation of those products.